ADM-assisted prepectoral breast reconstruction and skin reduction mastectomy: Expanding the indications for subcutaneous reconstruction. Issue 4 (April 2020) - Onesti, M.G.; Di Taranto, G.; Ribuffo, D.; Scuderi, N.
Summary: Backgrounds: Recently a flood of new techniques and studies have been released for prepectoral reconstruction, following strict criteria for selection of patients undergoing skin or nipple sparing mastectomy. Nevertheless a big population of patients that would otherwise benefit from prepectoral techniques has been excluded so far. Patients and methods: Between January 2016 and February 2017, patients undergoing skin reducing mastectomy (SRM) were enrolled at our Institution. We selected patients with large and ptotic (grade II-III) breasts undergoing SRM, followed by a new technique, which involves placement of the implant, wrapped by acellular dermal matrix, in a prepectoral pocket under a dermal flap. Data of all the surgeries were prospectively collected and contracture grade was assessed by Baker scale. Complication rate and cancer recurrence were reported and health related quality of life (HRQOL) measurement was recorded using BREAST-Q questionnaire. At early follow-up, postoperative pain was assessed through VAS scale. Results: 29 patients underwent SRM and 10 patients, meeting inclusions criteria, were enrolled, with a total of 13 operated breasts. Postoperative average pain was assessed as low as 4.1. The median follow-up was 2.6 (range 2.1–3.2) years. Post-operative complications occurred in 1 case of minimal wound dehiscence. No patient reported breast seroma or severe capsular contracture grade. Patient scored high level of satisfaction with breast, psychosocial well-being, sexual well-being, physical impact and overall satisfaction with outcome, at BREAST-Q questionnaire. Conclusions: In this study we present a modified prepectoral technique for patients undergoing SRM, reporting satisfactory outcomes. These results might support the rationale for expanding the population target of prepectoral reconstruction.